Tungsten carbide/porous carbon core–shell nanocomposites as a catalyst support for methanol oxidation. Issue 17 (2nd February 2016) - Lang, Xiaoling; Shi, Meiqin; Jiang, Yekun; Chen, Huan; Ma, Chunan
Abstract : The Pt–WC@C demonstrates higher electrochemical activity, which could be attributed to the better dispersed Pt on WC which leads to the improved synergistic effect between WC and Pt. Abstract : Carbon-encapsulated tungsten carbide (WC@C) was prepared by a microwave-assisted synthesis method with resorcinol-formaldehyde resin (RF) as carbon source. WC was encapsulated by porous carbon layer to form core–shell structure which could protect tungsten oxide from occupying the active sites on the surfaces of the WC@C. The characteristics of WC@C composites were determined by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, energy dispersive X-ray spectroscopy and Brunauer–Emmet–Teller gas adsorption. Platinum nanoparticles were uniformly distributed on WC@C to synthesize a new electrocatalyst Pt–WC@C. The electro-catalytic performances of prepared Pt–WC@C, commercial Pt/C and PtRu/C toward methanol oxidation were compared by cyclic voltammetry, chronoamperometry and CO stripping test. It was found that Pt–WC@C exhibited higher catalytic activity for methanol oxidation than that of commercial Pt/C and PtRu/C catalysts. Especially, the Pt–WC@C achieved the long-term stability which was attributed to the effective protection by the carbon porous shell structure.